2022
DOI: 10.1097/sla.0000000000005699
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of a Cost–Volume Relationship in Robotic-assisted Thoracoscopic Lung Resections

Abstract: Objective: To characterize the relationship between institutional robotic-assisted pulmonary lobectomy volume and hospitalization costs. Background: The high cost of robotic-assisted thoracoscopic surgery (RATS) is among several drivers of hesitation among nonadopters. Studies examining the impact of institutional experience on costs of RATS lobectomy are lacking. Methods: Adults undergoing RATS lobectomy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies have reported high overall robotic-assisted surgical volume to be associated with reduced costs for cancer surgery, including lobectomy, pancreaticoduodenectomy and prostatectomy. 11,12,18,19 In the present work on RAC, we found that an increase in the number of all robotic operations performed at a center was associated with decreased index hospitalization costs. This finding may be explained by the fact that centers with a high robotic operation volume also tend to be high-volume colectomy institutions.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies have reported high overall robotic-assisted surgical volume to be associated with reduced costs for cancer surgery, including lobectomy, pancreaticoduodenectomy and prostatectomy. 11,12,18,19 In the present work on RAC, we found that an increase in the number of all robotic operations performed at a center was associated with decreased index hospitalization costs. This finding may be explained by the fact that centers with a high robotic operation volume also tend to be high-volume colectomy institutions.…”
Section: Discussionmentioning
confidence: 58%
“…10 Prior work has revealed higher center-specific robotic surgical volume to be associated with lower costs for various cancer operations including lobectomy and pancreaticoduodenectomy. 11,12 Specifically, an increase in the overall robotic-assisted caseloads have been shown to reduce operative times and postoperative length of stay. 10 However, there is a paucity of data regarding the definition of high-volume for RAC as well as its associated cost-volume outcome relationship.…”
Section: Introductionmentioning
confidence: 99%